2021
DOI: 10.1136/bmjgh-2020-003455
|View full text |Cite
|
Sign up to set email alerts
|

Conference equity in global health: a systematic review of factors impacting LMIC representation at global health conferences

Abstract: IntroductionGlobal health conferences are important platforms for knowledge exchange, decision-making and personal and professional growth for attendees. Neocolonial patterns in global health at large and recent opinion reports indicate that stakeholders from low- and middle-income countries (LMICs) may be under-represented at such conferences. This study aims to describe the factors that impact LMIC representation at global health conferences.MethodsA systematic review of articles reporting factors determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
89
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 38 publications
0
89
0
4
Order By: Relevance
“…1 The growing calls to decolonise global health point to imbalances that contribute to the status quo in global health knowledge production: insufficient funding for research capacity building in the Global South, 2 domination of research activities by institutions and researchers from the Global North, 3 lack of fair credit to and representation of local authors in research publications, 4 prohibitive publication costs and little interest in local issues from global health journals, 5 and barriers faced by researchers from the Global South to participation in international conferences. 6 But more pernicious than all of these imbalances is the underlying and pervasive dehumanisation of Black and Brown (and other) people, 7 and the persistent white saviour mentality and related white or northern supremacy. 1 Although somewhat under the radar, the instrumental role of research funders in the perpetuation of the status quo in global health research must be addressed.…”
mentioning
confidence: 99%
“…1 The growing calls to decolonise global health point to imbalances that contribute to the status quo in global health knowledge production: insufficient funding for research capacity building in the Global South, 2 domination of research activities by institutions and researchers from the Global North, 3 lack of fair credit to and representation of local authors in research publications, 4 prohibitive publication costs and little interest in local issues from global health journals, 5 and barriers faced by researchers from the Global South to participation in international conferences. 6 But more pernicious than all of these imbalances is the underlying and pervasive dehumanisation of Black and Brown (and other) people, 7 and the persistent white saviour mentality and related white or northern supremacy. 1 Although somewhat under the radar, the instrumental role of research funders in the perpetuation of the status quo in global health research must be addressed.…”
mentioning
confidence: 99%
“…Unequal attendance at academic conferences has been documented. A recent systematic review by Velin and colleagues demonstrated that those from LMICs looking to attend global health conferences faced inequities related to cost, visas, and limited speaking opportunities that were less commonly encountered by attendees from HICs [40] . Given these limitations, the generalizability of the results may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…10 Inequalities in research output from LMICs may stem from multiple causes, ranging from limited funding, lack of research infrastructure, language barriers, limited research training, and competing clinical demands. 6,11,12 The preference for English in international journals may prevent nonnative speakers from more broadly disseminating their research. 13 The skill needed to thoroughly research a clinical question, the costs of accessing literature for background research, as well as the open access publishing fees may be additional barriers.…”
mentioning
confidence: 99%